Teachers Strategy in doing Listening Skill of CEFR B1 and B2 Level Test based on Self-Reflection - Nurlatifah, Ilma (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Listening is a receptive skill that plays a crucial role in learning English because it is a language modality used in direct conversation. This study utilized a narrative inquiry approach, a qualitative research method that gathers data through documentation, reflective notes, and participant interviews. Six students from MPBI Class C participated, providing self-reflections on their experiences with listening tasks and strategies. Data collection included detailed self-reflections, semi-structured interviews, and teacher reflective notes, ensuring a comprehensive understanding of the strategies' impact. The primary instrument used in this study was: Self-reflection, Students maintained journals documenting their thoughts, feelings, and observations regarding the listening strategies used in their classes. Interviews with students provided deeper insights into their reflections and allowed for clarification and elaboration on their written reflections. Thematic analysis was employed to analyze the data from self-reflections, interviews, and teacher notes. Key themes related to listening strategies, student experiences, and instructional practices were identified and categorized. Narrative construction techniques were used to create detailed accounts of each participant's experiences, which were then compared and contrasted to identify common patterns and differences. In conclusion, the teacher's strategies significantly benefited students' listening skills development at the CEFR B1 and B2 levels. This study highlights the importance of reflective practices, tailored instruction, and continuous feedback in enhancing language proficiency. explore whether there was a difference in this self-reflection of six levels of learning strategies between the different levels of their English proficiency.